2019
DOI: 10.1186/s12909-019-1823-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between perfectionism and symptoms of depression in medical school applicants

Abstract: Background The association between perfectionism and depression in the medical profession can ultimately influence physicians’ performance negatively. In medical students, especially maladaptive perfectionism is connected with distress and lower academic performance. The expression of perfectionism and symptoms of depression at the time of medical school application is not known. Therefore, we explored perfectionism and symptoms of depression in participants of multiple mini-interviews for medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…If students are entering the course with distress it is important to consider whether initial screening of candidates for psychological distress is appropriate [ 33 ]. It has been suggested that the addition of psychological screening may allow for selection of more resilient medical students [ 34 36 ]. Psychological screening is used in other high stress jobs such as police, military, and airline pilots [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…If students are entering the course with distress it is important to consider whether initial screening of candidates for psychological distress is appropriate [ 33 ]. It has been suggested that the addition of psychological screening may allow for selection of more resilient medical students [ 34 36 ]. Psychological screening is used in other high stress jobs such as police, military, and airline pilots [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diathesis-stress model could help explain why Zhongyong thinking could be related to college student’s emotion. Based on the diathesis-stress model, individuals with some personality traits, such as poor self-esteem ( Nguyen et al, 2019 ), low self-directedness and cooperativeness ( Lim et al, 2018 ), low agreeableness ( Roman et al, 2019 ), and high perfectionism ( Bußenius and Harendza, 2019 ), may predispose them to develop more depression and anxiety symptoms. Results from two cross-sectional studies demonstrated that Chinese adults with high level of Zhongyong thinking style had few depressive and anxiety symptoms ( Zhan et al, 2013 ; Yang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the Medical Faculty of Hamburg University, the selection process for medical school applicants includes a natural science test (HAM-Nat) in a first step [8] and multiple mini-interviews (HAM-Int) in a second step [9,10] besides high school grade point averages. We already detected that rejected applicants who participated in the multiple mini-interviews (HAM-Int) showed higher levels of depressive symptoms than admitted applicants [11]. This can be partly explained by maladaptive perfectionism [11], which is an important finding becausein contrastadaptive perfectionism [12] has been described to be highest in medical school applicants admitted by their grade point average only [13].…”
Section: Introductionmentioning
confidence: 90%
“…We already detected that rejected applicants who participated in the multiple mini-interviews (HAM-Int) showed higher levels of depressive symptoms than admitted applicants [11]. This can be partly explained by maladaptive perfectionism [11], which is an important finding becausein contrastadaptive perfectionism [12] has been described to be highest in medical school applicants admitted by their grade point average only [13]. Furthermore, adaptive perfectionism shows a general decrease during undergraduate medical studies independent of the admission procedure [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation